Study on fused/cast AZS refractories for deployment in vitrification of radioactive waste effluents - Sengupta, Pranesh; Mishra, Raman K.; Soudamini, N.; Sen, D.; Mazumder, S.; Kaushik, Chetan P.; Ajithkumar, Thalasseril G.; Banerjee, K. (Journal of Nuclear Materials, 2015)
Fused/cast Al2O3-ZrO2-SiO2 (FC-AZS)' is being considered as `glass contact refractory' within ceramic melters, to be used for nuclear waste immobilization. Microstructural analyses reveal random distributions of baddeleyite (ZrO2) within aluminosilicate (Al2SiO5) matrix. Al-27 and Si-29 NMR data suggest that within aluminosilicate matrix Al occurs in both 4- and 6-fold co-ordinations whereas Si prefers a 4-fold environment. Polydispersity of pores has been studied with small-angle neutron scattering (SANS) technique. Corrosion rates of FC-AZS within 6 M HNO3, simulated wastes (500 h exposure), and borosilicate melt (975 degrees C, 800 h exposure) are found to be 0.38 x 10(3) mu my(-1), 0.13 x 10(3) mu my(-1) and 4.75 x 10(3) mu my(-1) respectively. A comparison of chemical interaction data clearly suggests that FC-AZS exhibits better chemical durability than AZC refractory (Al2O3-ZrO2-Cr2O3, also used for similar purpose). Thermal cycling studies indicate that FC-AZS retains structural integrity (including compressive strength and density) even up to 20 cycles. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Interaction between refractory material and hazardous liquid; Nuclear waste immobilization; Vitrification melter